Imperfect Competition, Monetary Policy and Welfare in a Currency Area - Giovanni Lombardo (Deutsche Bundesbank, 2002)
This paper studies the implication, in terms of welfare and monetary policy, of unequal degrees of competition across members of a currency area. We look at two ways in which the degree of competition in the market for goods can affect welfare in a currency area. One is through different average degrees of competition in the monetary union; the other is through different degrees of competition across its members. We find two interesting results. First, if prices are sticky, more competition tends to be detrimental to welfare. Second, welfare increases in proportion to the asymmetry of the union. These results imply that the monetary authority should react more strongly to inflationary pressure coming from the more competitive member of the monetary union. We compute the optimal monetary policy of the central bank of the union and compare its performance with a simple Taylor rule. We discuss the circumstances under which the Taylor rule approaches the optimal rule. The optimal inflation target for the asymmetric union is also discussed. – – Dieses Papier untersucht die Auswirkung unterschiedlicher Wettbewerbsintensitäten in den Ländern eines Währungsraums auf die Wohlfahrt und die optimale Geldpolitik. Betrachtet werden zwei Möglichkeiten, wie die Wettbewerbsintensität am Gütermarkt die Wohlfahrt eines Währungsraums beeinflussen kann. Zwei interessante Schlussfolgerungen können gezogen werden. Erstens wirkt sich bei unflexiblen Preisen ein erhöhter Wettbewerb in der Regel negativ auf die Wohlfahrt aus. Zweitens kann die Geldpolitik effektiver sein, wenn die Länder größere Asymmetrien aufweisen. Diese Ergebnisse legen es nahe, dass die Zentralbank stärker auf einen Inflationsdruck reagieren sollte, der von dem Mitgliedsland ausgeht, in dem der Wettbewerb intensiver ist. Die optimale Geldpolitik der Zentralbank der Währungsunion wird ermittelt und mit einer einfachen Taylor-Regel verglichen. Es werden die Voraussetzungen erörtert, unter denen die Taylor-Regel sich der optimalen Regel annähert. Diskutiert wird auch das optimale Inflationsziel einer asymmetrischen Währungsunion.
Keywords: E5; E3; E4; F4; 330; Währungsraum; optimale Geldpolitik; Taylor-Regel; unvollständiger Wettbewerb; starre Preise; Currency area; optimal monetary policy; Taylor rule; imperfect competition; sticky prices; Währungsunion; Geldpolitik; Unvollkommener Wettbewerb; Preisrigidität; Inflationsbekämpfung; Taylor-Regel; Wohlfahrtseffekt; Theorie